Conservation of Groundwater by Absorbing Rainfall in the Ci Hideung Watershed - Dede Sugandi; Riki Ridwana; Arif Ismail (Universitas Pendidikan Indonesia, 2023)
This research aims to: analyze built-up area, rainfall potential, and the effort of groundwater conservation in the Ci Hideung watershed. An experimental method was done to discover the depth of groundwater. Landsat 8 Images are used to analyze the land cover. Rainfall volume is measured by formula; V = Rainfall.area, while the infiltration wells using formula: V = volume (m3).area. The infiltration measurement uses a double ring infiltrometer. Built-up land area are 1.563 km2 (14.77 %) and non built-up area are 9.022km2(85.27 %). The lowest rainfall potential to be absorbed is in May with a volume of 0.282 m3, while the highest is in November with a thickness of 2.912 m. Rainfall volume needs to be absorbed through the infiltration wells on the smallest land unit every 100 m2. The highest rainfall thickness is 2.912, then the volume of 302.40 mm3 was added to the infiltration wells with a length of 1 meter and a wide of 1 meter with a depth of 2.912 meters. Groundwater conservation is highly needed to increase groundwater supply. The highest rainfall volume of 302.40 mm3 could be absorbed in 2.91 hours (174.46 minutes) and the longest is in 3.64 hours. The infiltration wells have a role in storing rainfall to increase groundwater supply so that groundwater surface is also increased.